2009
DOI: 10.1016/j.cellbi.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of headless myosin X in the motility of immortalized gonadotropin‐releasing hormone neuronal cells

Abstract: Myosin X (Myo X), an unconventional myosin with a tail homology 4-band 4.1/ezrin/radixin/moesin (MyTH4-FERM) tail, is expressed ubiquitously in various mammalian tissues. In addition to the full-length Myo X (Myo X FL), a headless form is synthesized in the brain. So far, little is known about the function of this motor-less Myo X. In this study, the role of the headless Myo X was investigated in immortalized gonadotropin-releasing hormone (GnRH) neuronal cells, NLT. NLT cells overexpressing the headless Myo X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Headless Myo10 Is a Negative Regulator of Full-length Myo10-Since the discovery of headless Myo10, it has been widely hypothesized to function as an endogenous dominant negative of the full-length protein (28,30,31). This is consistent with our knockdown results showing opposite effects of full-length and headless Myo10 on axon outgrowth.…”
Section: Overexpression Of Full-length Myo10 Stimulates Axon Outgrowtsupporting
confidence: 83%
See 2 more Smart Citations
“…Headless Myo10 Is a Negative Regulator of Full-length Myo10-Since the discovery of headless Myo10, it has been widely hypothesized to function as an endogenous dominant negative of the full-length protein (28,30,31). This is consistent with our knockdown results showing opposite effects of full-length and headless Myo10 on axon outgrowth.…”
Section: Overexpression Of Full-length Myo10 Stimulates Axon Outgrowtsupporting
confidence: 83%
“…Myo10 knockdown also decreased filopodia and adhesions when the cells were cultured in vitro. Similarly, experiments with NLT cells, a neuronal cell line, showed that overexpression of a motorless Myo10 construct decreased migration and focal adhesion formation (30). The enrichment of Myo10 that we observed in the rostral migratory stream of the postnatal brain suggests that Myo10 may be important for the migration of some populations of neurons in the brain.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, Myo10 is highly regulated during development of the nervous system and exists in two forms (Sousa et al, 2006), the fulllength and the 'headless' isoform, which lacks the motor activity and is differently regulated during development (Sousa et al, 2006;Raines et al, 2012). Headless myosin is enriched in regions of proliferating and migrating cells (Raines et al, 2012), and was hypothesized to act as a dominant-negative isoform, regulating Myo10 full-length activity in neurons (Sousa et al, 2006;Zhu et al, 2007;Wang et al 2009). Consistent with this hypothesis, in cortical neurons, knockdown of full-length Myo10 reduces axon outgrowth, whereas knockdown of headless Myo10 increases axon outgrowth (Raines et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Headless Myo10 has been hypothesized to act either as a scaffolding molecule or as a naturally occurring dominant negative (Sousa et al, 2006). Although the numerous binding partners of Myo10, such as integrin, can make interpretation of dominantnegative approaches challenging, motorless Myo10 constructs clearly inhibit netrin-dependent axon outgrowth (Zhu et al, 2007) as well as formation of focal adhesions and chemotaxis in a neuronal cell line (Wang et al, 2009). Axon guidance depends on both actin and microtubules, with filopodia being especially important for axonal path-finding (Dent and Gertler, 2003).…”
Section: Functions Of Myo10 In Neuronsmentioning
confidence: 99%